2020
DOI: 10.1111/fcp.12546
|View full text |Cite
|
Sign up to set email alerts
|

Drug interactions related to self‐medication: a French pharmacovigilance database study

Abstract: Self‐medication (SM) is a common practice perceived by patients as harmless which can, however, entail health risks. The aim of the study was to identify drug–drug interactions (DDIs) involving SM drugs leading to adverse drug reactions (ADRs) in the National French Pharmacovigilance Database. All ADR reports from 1 January 1985 to 31 July 312018, coded as ‘interaction’ and ‘self‐medication’, were selected and studied. Patient characteristics, the level and type of interaction, and the therapeutic classes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In one study, 16.3% (No: 212) of self-medicating students developed side effects [13]. In another study, drug poisoning due to the simultaneous consumption of multiple drugs led to brain hemorrhage and ultimately death of an individual [12]. In this regard, arbitrary violation of the medications' instruction of use can be dangerous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, 16.3% (No: 212) of self-medicating students developed side effects [13]. In another study, drug poisoning due to the simultaneous consumption of multiple drugs led to brain hemorrhage and ultimately death of an individual [12]. In this regard, arbitrary violation of the medications' instruction of use can be dangerous.…”
Section: Discussionmentioning
confidence: 99%
“…The unreasonable use of medication can even lead to death. One study showed that, the simultaneous and arbitrary use of multiple medications causes some disorders in hemostasis, renal function, hemorrhagic stroke and death [12]. In another study, 32.3% of students, who had self-medication, developed side effects [13].…”
mentioning
confidence: 99%
“…Reasons for missing a potential DDI may be a lack of knowledge about DDIs, a lack of appropriate CDSS in the information system they are using, or due to missing correct information about a patient's current medications, or due to different perceptions about responsibility or lack of time to check for interactions [27][28][29]. DDIs can also occur because of the patient's self-medication, such as Over the Counter (OTC) medications or herbal drugs that patients buy themselves, or because of medically unapproved re-use of prescription drugs or the consumption of dietary supplements [30]. There is a need to increase awareness among patients regarding DDIs, especially related to self-medication [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…DDIs can also occur because of the patient's self-medication, such as Over the Counter (OTC) medications or herbal drugs that patients buy themselves, or because of medically unapproved re-use of prescription drugs or the consumption of dietary supplements [30]. There is a need to increase awareness among patients regarding DDIs, especially related to self-medication [30,31]. Written medication information to patients, such as a patient information leaflets (PIL) and online information sources, sometimes include DDI information [32].…”
Section: Introductionmentioning
confidence: 99%
“…Prescribers often do not have access to all prescriptions made by other HCP due to lack of interoperability between different EHRs [35]. Patients also use OTC (over the counter drugs, available without prescription) and herbal remedies on their own, which are not on their medication list [36]. Besides the challenge of lack of overview of a patient's medication, prescribers' knowledge of clinically relevant DDI may vary and there is need for support systems to identify DDI and adjust inappropriate combinations [3,7,34].…”
Section: Introductionmentioning
confidence: 99%